Writing Test with Image Processing Technique - Kamolchanok Charoy-boon; Nattakan Kruesang; Anuntapat Anuntachai; Natte Raksadawan (My University, 2023)
Nowadays, Dysgraphia frequently discovers as same as other intellectual disabilities. The dysgraphia diagnosis method is to do monitoring by human then this paper represents the applied technology for improving the diagnosis performance. The writing test is to estimate the writing ability and alphabet perception. The image processing is applied to evaluate writing test for students (grade 1–3 or 6–8 years). The student wrote sentences accordingly to an example article in a time frame. The example article composed of 4 lines, 40 words and 161 alphabets of Thai language.
Keywords: Writing and Handwriting Education; Reading and Literacy Development; Second Language Acquisition and Learning